THE NURSE'S WORK IN COLLECTIVE HEALTH AND STRESS: A REALITY'SANALYSIS - Rosane Teresinha Fontana; Kallyne Irion Siqueira (Universidade Federal do Paraná, 2009)
Descriptive, quantitative-qualitative study, which aimed to measure the stress of nurses in public health andinvestigate the influence of some individual and situational variables on working conditions. Data were collected throughthe application of a job stress range and a questionnaire with five non-structured questions to 11 nurses who work ascoordinators of Family Health Strategy Unit teams or other programs, in Basic Health Units in a city within the state of RioGrande do Sul, Brazil. From the analysis of data, subjects perceive adequately the demands of work, not showing significantlevels of work stress. It can be inferred that in the context studied, there are good general working conditions, which hasa positive influence on factors that generate stress.